Immobilization of saccharomyces cerevisiae onto cross-linked chitosan coated with magnetic nanoparticles for adsorption of uranium (VI) ions - Saifuddin N.; Dinara S. (2023)
Uranium mining contaminates surface and groundwater and therefore uranium removal from wastewater becomes very important. Among the many bioagents available, the most effective biosorbents is the yeast Saccharomyces Cerevisiae which is widely used in food industries, and multi-functional biopolymer Chitosan. The use of magnetic nanoparticles offers many advantages such as magnetic separation and heavy metal adsorption. Magnetic nanoparticles were obtained using microwave irradiation, and coated with cross-linked chitosan beads. Cross-linked chitosan beads were synthesized by the reacting chitosan with epichlorohydrin (ECH) and grafted with Saccharomyces Cerevisiae under microwave irradiation. Adsorption of uranium (VI) from aqueous solution onto adsorbent was investigated in a batch system. Adsorption isotherm and adsorption kinetic studies of uranium (VI) onto cross-linked chitosan were carried out in a batch system. The factors influencing uranium (VI) adsorption were investigated and described in detail, as a function of the parameters such as contact time, pH value, initial uranium (VI) concentration, adsorbent mass, reusability of adsorbent. The Saccharomyces cerevisiae-crosslinked chitosan-magnetic nanoparticle (SC-CTS-ECH-MNP) adsorbent showed best results for the fast adsorption of U (VI) from aqueous solution at initial pH value 4.0. In addition, more than 90% of U (VI) was removed within the first 20 min, and the time required to achieve the adsorption equilibrium was only 110 minutes. Langmuir and Freundlich adsorption models were used for the mathematical description of the adsorption equilibrium. Equilibrium data agreed very well with the Langmuir model, with a maximum adsorption capacity of 72.4 mg.g-1. Adsorption kinetics data were tested using pseudo-first-order and pseudo-second-order models. Kinetic studies showed that the adsorption followed a pseudo-second-order kinetic model, indicating that the chemical adsorption was the rate-limiting step.